Middle East and Central Asia Global Trends Impact on the Countries of the Region - Yendibay М.; Abzhapparova Б. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article examines the negative impact of global trends that have engulfed the world on the countries of the Middle East and Central Asia and the issue of ensuring security from threats. Currently, the impact on the Middle East and Central Asia of the problems of the economic crisis, inflation, unemployment, investment outflow, tension between Russia and Ukraine, the growth of conflict points in the regions, conflict between actors, etc. is being analyzed. Passive threats, known today in the Middle East and Central Asia and which in the future may overshadow its range, will also become the core of the article and will be subjected to serious analysis. Recently, an even greater aggravation of the situation between Israel and Palestine has been considered, as well as the intensification and strengthening of the Israeli military operation in the Gaza Strip, which the world is watching, and the aggravation of relations between the parties. The influence of external actors on regional trends in the Middle East and Central Asia is also analyzed.